Evidence for metabolite composition underlying consumer preference in sub-Saharan African Musa spp. - Drapal, M.; Amah, D.; Uwimana, Brigitte; Brown, A.; Swennen, R.; Fraser, P.D. (Elsevier, 2024)
Breeding programs for disease resistant bananas in Sub-Saharan Africa generated resistant bananas, which did not meet fruit quality characteristics preferred by consumers. The present study aimed to establish chemotypes underlying preferred cooking bananas of Matooke, Mchare and plantain and less preferred Mbidde bananas, used for beer brewing. The metabolite data of Mbidde showed higher levels of metabolites associated with sour, sweet, and astringent taste; as well as different textural properties associated with cell wall composition and lignin content. Significant differences in the majority of specialised and primary metabolites were observed in the pulp of cooking banana groups. Analysis of peel tissue indicated similar metabolic differences in the protective layer surrounding the pulp and suggested a distinct genetic regulation of phenylpropanoid and flavonoid pathways between the genome groups. In summary, the present data can be used to establish metabolic traits associated with consumer preference, which can augment modern breeding programs.